Seasonal variations in moderate-to-vigorous physical activity among children and adolescents with visual impairment during different segments of the school day - Li Dou; Huawei Chen; Yemao Xia; Enjie Lu (Frontiers in Public Health)
Background and objectiveThe seasonal variation in physical activity (PA) among children and adolescents with visual impairment (VI) is a significant public health concern, as they often experience unique barriers to engaging in regular PA. This study examines the seasonal variation in accelerometer-assessed PA among children and adolescents with VI during four distinct segments of the school day: physical education (PE) class, recess, lunchtime, and one-hour club time.Participants and methodsA total of 63 children and adolescents aged 7 to 17 years from a specialized VI school in eastern China participated in the study. PA was measured using ActiGraph® accelerometers during winter and summer in 2022–2023 academic year. A one-way analysis of variance (ANOVA) was performed to compare the effects of seasonal variation on the time spent on moderate-to-vigorous physical activity (MVPA) by children and adolescents with VI across the four segments of the school day. Additionally, linear mixed models were conducted to estimate seasonal variation in MVPA proportions.ResultsThe results revealed that children and adolescents with VI engaged in a higher level of MVPA during winter compared to summer. Across both seasons, primary students exhibited significantly higher cumulative MVPA than secondary students during four school day segments. PE classes were found to constitute the highest percentage of MVPA. Furthermore, the proportion of time spent in MVPA during winter was higher than in summer during recess and lunchtime. Gender differences were also noted, with boys exhibiting higher levels of MVPA than girls during recess and PE time. Additionally, grade-level differences were identified during recess, PE, and lunchtime.ConclusionThe findings suggest that seasonal factors should be considered when designing physical activity programs for children and adolescents with VI. In particular, more PE classes should be provided and strategies should be adopted to increase MVPA levels during recess and lunchtime in both seasons, which may help children and adolescents with VI to meet the internationally recommended PA standards. Future research should explore the underlying factors influencing seasonal variations in PA among this population and develop targeted interventions to promote MVPA engagement.